Investigation of shear stress distribution in a 90 degree channel bend - Lee, Seung Kyu; Dang, Truong An; Le, Van Tuan (Zielona Góra: Uniwersytet Zielonogórski)
Shear stress is a key parameter that plays an important role in sediment transport mechanisms; therefore, understanding shear stress distribution in rivers, and especially in river bends, is necessary to predict erosion, deposition mechanisms and lateral channel migration. The aim of this study is to analyze the shear stress distribution near a river bed at 90-degree channel bend using a depth-average method based on experimental measurement data.
Keywords: experimental channel; 90-degree bend; shear stress; erosion; deposition